WUJUD PRAGMATIK DEKLARATIF PEJABAT PUBLIK DALAM TINJAUAN FUNGSI BAHASA (STUDI KASUS PENGGUNAAN BAHASA CALON WALIKOTA BANDUNG TAHUN 2013) - Sunasih Mulianingsih (Institut Pemerintahan Dalam Negeri, 2017)
The declarative and the pragmatic form of public services in the context of language function assessed controverse, not polite, and showed problems among individuals or groups are not consumted by public anymore. This research describes analytically the pragmatic expression of the public leader, the Bandung municipal candidate. The metode used is an analytic descriptive with the teqnic of data collection involved documentation study, the records of Bandung municipal candidate’s expressions in campange. This research showed that the politic statement of public leader becoming the Bandung municipal candidate has already completed the politeness of the languge. It connected with after the compange over there is no indication from public as the demonstrant. The form of the pragmatic and declarative has completed the politeness of the language. As the recommendation from the research are thelanguage communicated by the public leader having been polite is better kept or progressed. It showed public leaders are figure who will be imitated by the public in the case of language expressions (statements) Keywords: pragmatic, declarative, public leaders